(untitled) (Eurasian Medical Research Periodical, 2024)
Lesions and severity of CHD are also associated with the occurrence of FP. Several studies have found a significant correlation between right coronary artery (RCA) infarction or lesion and VVFP [15,17,18]. Controversially, several studies have shown that patients with VVFP are more likely to have left main coronary artery disease (MI). PURPOSE: To evaluate the features of coronary artery lesions in patients with atrial fibrillation and anterior and inferior wall myocardial infarction of the left ventricle. Results of the study: To reveal the localization and degree of coronary artery (CA) lesions we performed coronary angiography in 124 patients with AMI of anterior and inferior localization accompanied by FP. Among the patients with AMI+FP there were significantly more patients with high risk of cardiovascular complications. In particular, among AMI patients with inferior myocardial wall lesions+FP.